Judo specific fitness test performance variation from morning to evening: specific warm-ups impacts performance and its diurnal amplitude in female judokas - Eken, Ö.; Clemente, F. M.; Nobari, H. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background A number of specific tests are used to standardize competition performance. Specific Judo fitness test (SJFT) can be applied by considering the start of the competition qualifiers in the morning and the continuation of the final competitions in the evening. The improvement of test performances can be achieved with warm-up for elevating heart rate (HR) and muscle temperature such as raise, activate, mobilise, potentiate (RAMP) protocols.